Accuracy And Error Study Of Horizontal And Vertical Measurements With Single View Metrology For Road Surveying - Hoo, Jian Ea; Lim, Kim Chuan (Asian Research Publishing Network (ARPN), 2016)
High quality digital image can be produced and stored with cost effective embedded system, thanks to advancement of low power digital camera and hardware accelerated high definition video image compression System-on- Chip. Image recorded with these multi-megapixel digital cameras allowed the world to be digitized more accurately (compared with conventional VGA camera with low resolution) and hence enable the use of single image as the metrology tool. Using the single view geometry techniques (planar homography, vanishing points and vanishing lines) widely accepted by the community, the suitability of applying these techniques with error reduced for road surveying is studied and reported in this work.